2006
DOI: 10.1165/rcmb.2005-0289oc
|View full text |Cite
|
Sign up to set email alerts
|

Role of Prostacyclin versus Peroxisome Proliferator-Activated Receptor β Receptors in Prostacyclin Sensing by Lung Fibroblasts

Abstract: Prostacyclin and its mimetics are used therapeutically for the treatment of pulmonary hypertension. These drugs act via cell surface prostacyclin receptors (IP receptors); however, some of them can also activate the nuclear receptor peroxisome proliferator-activated receptor beta (PPARbeta). We examined the possibility that PPARbeta is a therapeutic target for the treatment of pulmonary hypertension. Using the newly approved (for pulmonary hypertension) prostacyclin mimetic treprostinil sodium, reporter gene a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
66
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(70 citation statements)
references
References 17 publications
4
66
0
Order By: Relevance
“…18 Interestingly, another PGI 2 analogue, treprostinil, also inhibits the proliferation of human and mouse primary lung fibroblasts through the activation of a peroxisome proliferator-activated receptor-␤/␦ when used in equivalent doses. 19 These observations suggest that high levels of PGI 2 may attenuate PA remodeling in vivo through antiproliferative effects. Consistent with previous studies, we demonstrated that high levels of endogenous PGI 2 successfully attenuated medial hypertrophy of the PA. 3,4,6 To discover new drug targets, the roles of peroxisome proliferator-activated receptors and high-level PGI 2 in PAH therapy should be determined, because peroxisome proliferator-activated receptors are associated with many inflammatory and proliferative disorders, including PAH.…”
Section: Discussionmentioning
confidence: 92%
“…18 Interestingly, another PGI 2 analogue, treprostinil, also inhibits the proliferation of human and mouse primary lung fibroblasts through the activation of a peroxisome proliferator-activated receptor-␤/␦ when used in equivalent doses. 19 These observations suggest that high levels of PGI 2 may attenuate PA remodeling in vivo through antiproliferative effects. Consistent with previous studies, we demonstrated that high levels of endogenous PGI 2 successfully attenuated medial hypertrophy of the PA. 3,4,6 To discover new drug targets, the roles of peroxisome proliferator-activated receptors and high-level PGI 2 in PAH therapy should be determined, because peroxisome proliferator-activated receptors are associated with many inflammatory and proliferative disorders, including PAH.…”
Section: Discussionmentioning
confidence: 92%
“…Apart from this, prostacyclins inhibit the production of various cytokines and inflammatory mediators and suppress neutrophil adhesion [8,43]. It has been shown that treprostinil mediates antiproliferative mechanisms of resident lung fibroblasts [44]. Another prostacyclin analogue, iloprost was shown to have a beneficial effect in asthma [45].…”
Section: Discussionmentioning
confidence: 99%
“…In marked contrast, G i -coupled IP receptors were found exclusively in human erythroleukemia HEL cells with respect to STAT1 and STAT3 phosphorylation (Lo et al, 2006) and rat medullary thick ascending limb cells . Finally, but beyond the intended scope of this review, there are reports claiming that prostacyclin interacts with peroxisome proliferator-activated receptors to exert a portion of its activities (Lim and Dey, 2002;Ali et al, 2006).…”
Section: Ip Receptorsmentioning
confidence: 99%
“…Finally, IP(Ϫ/Ϫ) mice were used to distinguish some actions of PGI analogs on IP and PPAR␤. Ali et al (2006) used lung fibroblasts from IP(Ϫ/Ϫ) mice and those from PPAR␤(Ϫ/Ϫ) mice, examined inhibitory effects of treprostinil on their proliferation, and found that this activity was lost in PPAR␤(Ϫ/Ϫ) cells but not in IP(Ϫ/Ϫ) cells.…”
mentioning
confidence: 99%